20-year Results of a 3D Titanium Mesh Coating Stability of 31 Artificial Cups - Koch, Katharina; Nolte, Ingo; Hahn, Michael; Becker, Andreas (The Journal of Hip Surgery, 2024)
Background The aim of this work was to demonstrate the bony bond strength and resilience of a three-dimensional titanium mesh coating of an artificial acetabulum produced using the diffusion bonding technique. Under the extreme conditions ranging from abrasion-related osteolysis to acetabular perforation, the degree of residual bone and the integrity of the coating were determined. The remaining zones of the (still) stable bone connection are inevitably exposed to a greater load of the layer adhesion between the titanium mesh and the core shell. The investigation was intended to provide information about the stages of damage according to Paprosky in which it was still justifiable to leave the implant in place and simply change the inlay from the purely material-technical point of view of a stable coating. The bond between bone and implant was examined with regard to a possible retention of the implant for its adaptive remodeling up to 27 years.Materials and Methods In a retrospective study, 31 explanted human acetabular cups of the Harris-Galante II type, with an average lifetime of 19.7 years (11–27 years), were examined by means of digital area measurement to determine both the bone areas remaining on the coating and the damaged areas of the titanium mesh. Periacetabular bone loss was recorded in a modified Paprosky (PAP) damage classification. Full hemispherical sections of 4 acetabular cups with a life time of 16, 20, 22 and 27 years were examined histopathologically using the diamond cut technique.Results The periacetabular bone loss resulted in damage class PAP I in 8 cases, PAP IIa in 7 cases, PAP IIb in 2 cases, PAP IIc in 9 cases, PAP IIIa in 3 cases and PAP IIIa in 2 cases PAP IIIb. The average amount of bone that was still firmly attached to the coating after explantation was 17% (0–70%) of the total cup surface. Paprosky I accounted for 44.1%, and PAP IIa and IIb stadiums together a total of 17.1%. The average bone fraction of the implants no longer anchored in the host bed at stages IIc, IIIa and IIIb was 2%. The average coating damage was 11% (0–100%) and was exclusively attributable to the unstable implants of stages IIc, IIIa and IIIb. The histopathological findings showed adaptive bone remodeling, that was detectable for up to 27 years through the titanium mesh down to the interface with the solid acetabular core. The titanium wire mesh was mostly surrounded by lamellar, mature bone.Conclusion The results show that the connection between the Tivanium cup and the previously oldest and unchanged sintered coating – in the form of a three-dimensional titanium mesh applied in point and line contact – is very load-resistant even under the extreme loads of periacetabular osteolysis and cup perforations. Since there was no damage to the coating in periacetabular damage stages Paprosky I, IIa and IIb, it is justifiable in these damage stages to leave the implant in situ and to continue to use it with sole replacement of the inlay, but leaving the socket shell. The third-generation acetabular cup (Trilogy) with unchanged three-dimensional titanium mesh coating has been implanted in over 1.2 million cases for 26 years. After a long service life, an increasing number of wear and tear conditions can be expected in today's mostly elderly and vulnerable patient clientele. In view of the results presented here, the early detection of damage would make it possible to avoid costly and stressful explantation of the entire acetabular cup in favor of replacing the sole inlay in Paprosky stages I, IIa and IIb.
Keywords: titanium fibermesh coating; layer adhesion; artificial hip socket